2021
DOI: 10.1111/dme.14755
|View full text |Cite
|
Sign up to set email alerts
|

Current provision and HCP experiences of remote care delivery and diabetes technology training for people with type 1 diabetes in the UK during the COVID‐19 pandemic

Abstract: Background:The COVID-19 pandemic has led to the rapid implementation of remote care delivery in type 1 diabetes. We studied current modes of care delivery, healthcare professional experiences and impact on insulin pump training in type 1 diabetes care in the United Kingdom (UK). Methods:The UK Diabetes Technology Network designed a 48-question survey aimed at healthcare professionals providing care in type 1 diabetes.Results: One hundred and forty-three healthcare professionals (48% diabetes physicians, 52% di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Remote device training has been successful in comparison with in-person training, as shown by Vigersky et al [18 ▪ ] and Gómez et al [19 ▪ ] when conducting Medtronic 670G training through telemedicine. In the United Kingdom, 143 healthcare providers were surveyed and during the first year of the COVID-19 pandemic, the majority had reduced or significantly reduced new pumps starts (42 and 31%, respectively) which was due in part to lack of patient digital literacy, limited provider experience, and the time requirement of the patient [20 ▪ ]. However, the healthcare provider respondents also agreed that virtual device training would likely continue beyond the pandemic and overall had positive responses regarding the likelihood of performing future pump starts and pump renewals remotely.…”
Section: Telemedicine Use For Diabetes Device Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote device training has been successful in comparison with in-person training, as shown by Vigersky et al [18 ▪ ] and Gómez et al [19 ▪ ] when conducting Medtronic 670G training through telemedicine. In the United Kingdom, 143 healthcare providers were surveyed and during the first year of the COVID-19 pandemic, the majority had reduced or significantly reduced new pumps starts (42 and 31%, respectively) which was due in part to lack of patient digital literacy, limited provider experience, and the time requirement of the patient [20 ▪ ]. However, the healthcare provider respondents also agreed that virtual device training would likely continue beyond the pandemic and overall had positive responses regarding the likelihood of performing future pump starts and pump renewals remotely.…”
Section: Telemedicine Use For Diabetes Device Trainingmentioning
confidence: 99%
“…In addition, the perceived quality of care and technology barriers were common reasons not to use telemedicine. Although patient access to telemedicine software and internet is a significant barrier to telemedicine care, the ability to provide diabetes device data for healthcare provider review is critical for conducting a thorough and productive T1D clinical visit [20 ▪ ].…”
Section: Barriers To Telemedicine Usementioning
confidence: 99%
“…Diabetes lends itself well to remote healthcare provision, as cloud‐connected technologies including continuous glucose monitoring devices facilitate data sharing between the person with diabetes and their clinical team. Although not suitable for everyone, remote consultations have the potential to improve access to, and the efficiency of, our outpatient clinics as they tend to be shorter than face‐to‐face reviews 2,3 . Indeed, a previous meta‐analysis confirmed that telemedicine interventions in diabetes were associated with greater reductions in glycated haemoglobins (HbA1c) compared to usual care 4 …”
Section: Figurementioning
confidence: 99%
“…4 In the UK, the majority of remote diabetes consultations are conducted over the telephone, with some conducted using video. 3 Video consultations offer some advantages over telephone, including a more personal interaction with enhanced audio/visual cues and data sharing capabilities with opportunities for education. However, their technical requirements are more complicated and time requirements are usually longer.…”
mentioning
confidence: 99%
“…Diabetes technology has shown rapid growth such as continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM) diabetes delivery over the last decade (Dovc et al, 2020). This growth has expanded due to the COVID-19 pandemic and led to the rapid implementation of remote care delivery (Forde et al, 2022), which accelerated the implementation of platforms such a telemedicine (Wake et al, 2020).…”
Section: Introduction and Literaturementioning
confidence: 99%